2015
DOI: 10.15835/nsb.7.3.9532
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Magnetic Treatment of Irrigation Water on the Growth and Yield of Tomato

Abstract: This study was carried out to determine whether magnetic treatment of the irrigation water may actually enhance vegetative growth and yield of tomato. Three magnetic flux densities of 124, 319 and 719 G (treatments T1, T2 and T3) were used to treat the water and a control experiment (Tc) which was irrigated with non-magnetically treated water was also set up. The magnetic field was produced by an electromagnet that had a variable voltage unit varying the voltage from 4 to 12 V. The tomato were planted in bucke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 9 publications
4
12
1
Order By: Relevance
“…It increases electroconductivity, the solubility of salts and decrease pH moreover it plays an important role in insecticides, fungicides and herbicides, as well as, magnetized water caused increments in microorganism's number which reflected on the positive effect of the aforementioned parameters. These results agree with those recorded by Abd El-latif et al (2015), Yusuf and Ogunlela (2015) and Abdel .…”
Section: Effect Of Irrigation Watersupporting
confidence: 93%
See 1 more Smart Citation
“…It increases electroconductivity, the solubility of salts and decrease pH moreover it plays an important role in insecticides, fungicides and herbicides, as well as, magnetized water caused increments in microorganism's number which reflected on the positive effect of the aforementioned parameters. These results agree with those recorded by Abd El-latif et al (2015), Yusuf and Ogunlela (2015) and Abdel .…”
Section: Effect Of Irrigation Watersupporting
confidence: 93%
“…Meanwhile, Elsayed (2014) obtained that irrigation broad bean plants with magnetized water caused significant increments in chlorophylls, carotenoids and photosynthetic activity over the irrigation by normal water. Yusuf and Ogunlela (2015) reported that irrigation with magnetized water affected the vegetative growth of tomato by inducing the rate of growth, decrease the time to maturity and enhanced yield. By the same token, Abd El-latif et al (2015) on strawberry showed that irrigation with magnetized water + 50% NPK of recommended dose gave the maximum values of chlorophylls, carbohydrates, yield and TSS.…”
Section: Introductionmentioning
confidence: 99%
“…The value of tTab was obtained from Montgomery et al (1998). The result obtained in this study was in agreement with the work conducted by the previous researchers that MTW increased yield as shown in Figure 4 (Maheshwari and Grewal, 2009;Babu, 2010;Hozayn and Abdul-Qados, 2010;Dhawi, 2014& Ogunlela, 2017b.…”
Section: Yield Of Maize In Transparent Garden Shedsupporting
confidence: 92%
“…Sum of square treatment (SST R ), Sum of square total (SST O ), Correction factor (C.F) and Sum of square error (SS E ) were computed using Equations (9), (10), (11) and (12), respectively. The Analysis of Variance (ANOVA) was based on values generated from Equations (9), (10) and (12). (12) where T i is the total yield of each treatment, t is the number of treatments used, X is the individual yield based on the treatment used, G is the total yield from all the treatments used and N is the number of observation which is equal to the product of number of treatments (t) and number replications (r)…”
Section: Statistical Analysis By Completely Randomized Design (Crd)mentioning
confidence: 99%
“…[11] pointed out that magnetic treatment of irrigation water could alleviate adverse effect of water stress (water shortage) in crop because it reduces free radicals production and antioxidant enzymes activity. Magnetically-treated water increases evapotranspiration rate and water use efficiency [12]. This means that crop irrigated with magnetically-treated water could withstand water shortage, absorb little water available in the soil and the yield is not affected as crop irrigated with non magnetically-treated water.…”
Section: Introductionmentioning
confidence: 99%